Бюджетні аспекти реформування системи охорони здоров’я в Україні - Щербина, І.Ф. (Інститут демографії та соціальних досліджень НАН України, 2007)
На основе данных Государственного казначейства Украины и условий законодательства в статье анализируется существующий механизм бюджетного финансирования здравоохранения, включая все части бюджетной системы и системы межбюджетных отношений. Согласно данным анализа, автор делает заключение относительно недостатков бюджетной системы, затрагивающих качество и пригодность медицинских услуг для населения, и предлагает пути усовершенствования системы. On the basis of State Treasury of Ukraine data and of provisions of legislation, the article analyzes current budget mechanism of budget funding of health care including all parts of budget system and system of inter-budgetary relations. According to the analysis data, the author makes conclusions as to the shortcomings of the budget system that affect the quality and availability of the medical services to the population and proposes ways of the system im provement.